The Role of the Prefrontal Cortex and Functional Connectivity during Maritime Operations: An fNIRS study. Issue 1 (4th November 2020) - Fan, Shiqi; Blanco‐Davis, Eduardo; Zhang, Jinfen; Bury, Alan; Warren, Jonathan; Yang, Zaili; Yan, Xinping; Wang, Jin; Fairclough, Stephen
Abstract: Introduction: Watchkeeping is a significant activity during maritime operations, and failures of sustained attention and decision‐making can increase the likelihood of a collision. Methods: A study was conducted in a ship bridge simulator where 40 participants (20 experienced/20 inexperienced) performed: (1) a 20‐min period of sustained attention to locate a target vessel and (2) a 10‐min period of decision‐making/action selection to perform an evasive maneuver. Half of the participants also performed an additional task of verbally reporting the position of their vessel. Activation of the prefrontal cortex (PFC) was captured via a 15‐channel functional near‐infrared spectroscopy (fNIRS) montage, and measures of functional connectivity were calculated frontal using graph‐theoretic measures. Results: Neurovascular activation of right lateral area of the PFC decreased during sustained attention and increased during decision‐making. The graph‐theoretic analysis revealed that density declined during decision‐making in comparison with the previous period of sustained attention, while local clustering declined during sustained attention and increased when participants prepared their evasive maneuver. A regression analysis revealed an association between network measures and behavioral outcomes, with respect to spotting the target vessel and making an evasive maneuver. Conclusions: The right lateral area of the PFC is sensitive to watchkeeping and decision‐making during operational performance. Graph‐theoretic measures allow us to quantify patterns of functional connectivity and were predictive of safety‐critical performance. Abstract : fNIRS was used in a ship bridge simulator to study safety‐related performance during watchkeeping and decision‐making. Functional connectivity of the prefrontal cortex was measured. It was found that connection density was reduced during decision‐making while local clustering increased; connectivity measures were also significantly predictive of safety‐related behaviour.